2014
DOI: 10.1080/00032719.2014.979355
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 3-Amino-2-oxazolidinone in Animal Tissue by an Enzyme-Linked Immunosorbent Assay and a Time-Resolved Fluoroimmunoassay

Abstract: An indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) and a time-resolved fluoroimmunoassay (TR-FIA) for the determination of the furazolidone metabolite 3-amino-2-oxazolidinone (AOZ) were developed. 3-Amino-2-oxazolidinone was detected using its derivative, 3-[[(2-nitrophenyl)-methylene]-amino]-2-oxazolidinone (NPAOZ). 3-([(3-Carboxyphenyl)methylene]-amino)-2-oxazolidinone (CPAOZ) was used as the immunizing hapten for the production of monoclonal antibodies against NPAOZ. The ic-ELISA had a 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Gold chloride was provided by Sigma Company (St. Louis, MO, USA). Artificial antigen of CPAOZ-Bovine serum albumin (CPAOZ-BSA) conjugates, purifying anti-NPAOZ monoclonal antibodies (McAbs) was produced in our laboratory (Le & Yu, 2015). All other chemicals and organic solvents were of analytical grade or better.…”
Section: Materials and Reagentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gold chloride was provided by Sigma Company (St. Louis, MO, USA). Artificial antigen of CPAOZ-Bovine serum albumin (CPAOZ-BSA) conjugates, purifying anti-NPAOZ monoclonal antibodies (McAbs) was produced in our laboratory (Le & Yu, 2015). All other chemicals and organic solvents were of analytical grade or better.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…The results showed that the ICTS is reliable for the quantitative detection of AOZ residue in animal tissue samples. Compared with the enzyme-linked immunosorbent assay method developed by Liu et al (2010), Zhu et al (2010), Jester et al (2014, and Le and Yu (2015), the ICTS could also help save time without losing accuracy and precision.…”
Section: Fortified Sample Analysis and Comparison Of Icst With Lc-ms/msmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunological analytical methods are also used to detect furazolidone residues, including enzyme-linked immunosorbent assays (ELISAs) and colloidal gold immunochromatographic assays. The immunoassay method has the advantages of rapidity, high sensitivity, high specificity, and high throughput (Gu, Liu, Song, Kuang, & Xu, 2016;Liu et al, 2010;Peng, Song, Liu, Kuang, & Xu, 2016), so many ELISAs have been developed to detect AOZ in aquatic animals, chicken, pork, beef, and eggs (Chang, Peng, Wu, Wang, & Yuan, 2008;Cheng et al, 2009;Cooper et al, 2004;Franek et al, 2006;Jester, Abraham, Wang, El Said, & Plakas, 2014;Le & Yu, 2015;Liu et al, 2010;Vass et al, 2005). Nonetheless, the ELISA is relatively cumbersome and requires expertise.…”
Section: Introductionmentioning
confidence: 99%